Exopolysaccharides from Enterococcus faecium and Streptococcus thermophilus: Bioactivities, gut microbiome effects, and fermented milk rheology - Tarique, Mohammed; Ali, Abdelmoneim H.; Kizhakkayil, Jaleel; Liu, Shao-Quan; Oz, Fatih; Dertli, Enes; Kamal-Eldin, Afaf; Ayyash, Mutamed (ELSEVIER, 2024)
Exopolysaccharides (EPSs) are carbohydrate polymers that can be produced from probiotic bacteria. This study characterized the EPSs from Enterococcus faecium (EPS-LB13) and Streptococcus thermophilus (EPS-MLB10) and evaluated their biological and technological potential. The EPSs had high molecular weight and different monosaccharide compositions. The EPSs exhibited various biological activities at 250 mg/L, such as scavenging free radicals (10 % to 88.8 %), enhancing antioxidant capacity (714 to 2848 mu g/mL), inhibiting pathogens (53 % to 74 %), and suppressing enzymes and cancer cells (2 % to 83 %), etc. The EPSs supported the growth of beneficial gut bacteria from Proteobacteria, Bacteroidetes, Firmicutes, and Acinetobacter in fecal fermentation with total Short-chain fatty acids production from 5548 to 6023 PPM. Moreover, the EPSs reduced the gelation time of fermented skimmed bovine milk by more than half. These results suggest that the EPSs from LB13 and MLB10 have promising applications in the dairy and pharmaceutical industries.
Keywords: Exopolysaccharides; Bioactive functions; Prebiotics; Gut Microbiome; IN-VITRO; BACTERIA; HEALTH; Chemistry; Food Science & Technology